Multimodal Discourse Interpretation of the Paris Olympics Mascot - Xu, Longhua; Wang, Lei; Luo, Yanni (Quality in Sport, 2024)
Background: This study aims to analyze the design intention of the mascot of the Paris Olympics from a multimodal perspective. As the host of the 2024 Olympic Games, Paris' mascot carries rich meanings. With globalization and technological advancement, information spreads multimodally, and multimodal discourse analysis is important to understand how the mascot interacts with different audiences, conveys meanings as well as bridges cultural differences, and spreads the Olympic spirit and cultural heritage of the host country. Methods: Taking Kress and Van Leeuwen's visual grammar as the theoretical basis, based on multimodal discourse analysis under the perspective of social semiotics, and combining with the analysis indexes in the multimodal image analysis software, the mascots of the Paris Olympic Games are visualized and interpreted to explore their image characteristics, design concepts and social significance. Results: the mascot is analyzed from three aspects: reproduction meaning, composition meaning and interaction meaning. In terms of reproduction, the mascot is related to the Olympic Games and French culture; in terms of composition, the emblem and other elements are the core information carrier, and the color and other elements play an important role; in terms of interaction, the mascot has a variety of interactions with the viewers and so on. Conclusion: Olympic mascots are important components of Olympic culture. The multimodal discourse analysis comprehensively and accurately interpreted the connotation of the mascot of the Paris Olympic Games, reflecting the information of the organizing country and integrating it with the Olympic movement, reflecting the spirit of sports. The study has deficiencies, and the mascots can be further explored in the real context.